Evaluation of the antenatal care service program at the Pucang Sewu health center in Surabaya - Setiawan, Aris Rendy; Mustofa, Amirul; Haryati, Eny (Universitas Merdeka Malang, 2023)
Pregnant women receive ANC before birth. It builds trust with pregnant women, detects life-threatening issues, prepares for birth, and educates them about health. This study aims to describe and analyze the results of the successful implementation of the ANC program at the Pucang Sewu Health Center. This study uses a qualitative method. Data collection techniques were carried out using interview techniques and documentation. Then, after the data is collected, an interactive analysis is carried out. The results of this study indicate that the ANC program is successful. That is evidenced by the effectiveness of providing services to pregnant women so that the implementation of the program is realized comprehensively and in quality.Indicators of effectiveness in terms of output show that work plans have been prepared, activities implemented and evaluations carried out. In terms of outcomes, it can be seen from the success of the service program through reducing mortality, morbidity and improving nutritional status. The researcher's recommendation is to increase the efficacy by maximizing the quality of existing human resources, implementing training in handling mothers during the period, raising awareness of adequacy by maximizing existing facilities and infrastructure, holding socialization, and placing posters on the importance of the program in public places.